Heavy ion acceleration at dipolarization fronts in planetary magnetotails. Issue 20 (24th October 2015) - Greco, A.; Artemyev, A.; Zimbardo, G.
Abstract: Transient reconnection events in planetary magnetotails give rise to fast plasma jets, whose leading edges are called dipolarization fronts. We perform a test particle simulation of the acceleration of several ion species (H +, He +, and O + ) in a 2‐D model of dipolarization fronts. We study the dependence of the acceleration on parameters of the model, finding, e.g., that the average ion energy increases with the front velocity and with the initial injection energy. When the ion species are initially cold, O + ions get the largest amount of average energy. Conversely, when the injection energy of O + ions is increased, their average energy gain does not exceed that of the lighter species, suggesting that ion energization at local dipolarization fronts strongly depends on the initial particle gyroradius. Further, the energy gained by the most energetic fraction of particles scales approximately as the square root of the mass ratio. Key Points: We study heavy ion acceleration in a 2‐D model of dipolarization front Ion energization at local dipolarization fronts strongly depends on initial particle gyroradius Our modeling shows that heavy ions are accelerated more effectively than protons